RESILIENSI CAREGIVER PADA LANSIA DENGAN SKIZOFRENIA - Afriany, Aulia (Jurusan Psikologi FKIP Universitas Halu Oleo, 2024)
Abstract: This study aims to determine the sources of family caregiver resilience in the elderly with schizophrenia. Elderly is the longest span of life that individuals go through, being a caregiver for the elderly with schizophrenia has a special burden for the family. The role of caregivers is important in seeking healing and stability in the lives of elderly patients in society. The research subjects were family members who had cared for people with schizophrenia in the past year. The research was conducted using qualitative methods, and subject interview data were analyzed using a phenomenological approach. Five key themes were found related to the resilience of family caregivers in the elderly with schizophrenia, namely caregivers understanding patient disorders, caregiver commitment to healing, caregivers learning coping skills, interpreting positive parenting experiences, and forming a sense of mutual support among family members. Caregiver resilience can be increased by early intervention in the family to find out the health status and possible care that can be carried out by the family, support the knowledge and skills of care, and improve the caregiver support network.